Left ventricular false tendons and early repolarization: Preliminary study. (24th June 2020) - Pereira, A; Castanheira, J
Abstract: Introduction The early repolarization (ER) is an electrocardiographic (ECG) pattern that includes J wave slurring or notching, ST segment elevation and symmetrical high-voltage T waves in more than one lead. Frequently it appears in the left lateral leads and less commonly in inferior leads. It was first described as benign and it affects 10% of the global population. False tendons (FT) are fibromuscular structures variable in length, thickness and insertion. Normally, they have conductive tissue as a His bundle extension. It's more frequent in males and young athletes, and some diseases have been associated to them like ventricular arrhythmias and repolarization changes. Generally, there are two groups, longitudinal and transverse. The ECG in the first one shows more frequently ER with notching in the inferior leads and in the second one, slurring in infero-lateral leads. Objectives This study aims to investigate the association between the type of FT and ER. Methodology A total of 24 patients with FT and with no significant cardiac disease were included in an observational and descriptive cross-sectional study. All participants performed an ECG and cardiac ultrasonography in a single centre. Patients with abnormal ECGs were excluded Results Mean participant's age was 55 years old (range: 18-73), and 67% were males. ER was identified in 53%, and 56% of the participants with transverse tendons presented slurring in the inferior (33%) and in the lateral leads (33%). Longitudinal tendons were associated with ECG notching in 25% or slurring in 26.5%, mainly in the inferior leads (33%). Conclusion In this study, ER pattern in the inferior leads was a common finding in participants with longitudinal FT. No association between ER and type of FT was observed. An association between the transverse FT and the type of wall and slurring was observed.